Cosmological Conundrums A Conversation with Justin Khoury. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Justin Khoury, Professor of Physics at the University of Pennsylvania. This thought-provoking conversation gives a window into the world of a practicing cosmologist and examines a wide range of fascinating topics that his research covers such as the early universe, the Big Bang, dark matter, dark energy, Cosmic Microwave Background, the MOND (Modified Newtonian Dynamics) theory, and more.This carefully-edited book includes an introduction, Into The Light, and questions for discussion at the end of each chapter. How.